Joey: the Mechanical Boy - Brown Ash, M.; Mercer, Leah; Miolin, Philip; Lui, J. (The Nest Ensemble, 2014)
Writers: Leah Mercer & Margi Brown Ash // Director: Leah Mercer // Designer: Tessa Darcey // Lighting Designer: Karen Cook // Sound Designer: Joe Lui // Stage Manager: Jessica Harlond-Kenny // Featuring: Philip Miolin, Margi Brown Ash